High prevalence of antibiotic resistance in commensal Escherichia coli from healthy human sources in community settings - Nji Emmanuel; Kazibwe Joseph; Owusu-Dabo Ellis; Hambridge Thomas; Joko Alia Carolyn.....et al (Springer Nature, 2023)
This article is published by Springer Nature and is also available at https://doi.org/10.1038/s41598-021-82693-4